ANALISIS PENYERAPAN TENAGA KERJA PADA SEKTOR INDUSTRI PARIWISATA - Jannah, Nur Jannah Al Baiti; Nasution, Annio Indah Lestari; Syakir, Ahmad (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2023)
This research aims to find out and analyze how labor absorption is influenced by variables from the tourism industry in hotels such as the number of tourists, number of hotel rooms and wage levels in the tourism industry sector in Medan City. This type of research is quantitative descriptive research that uses secondary data with the data source coming from the Medan City Central Statistics Agency. In this research, the time period used ranges from 2017-2021. The analytical method used is multiple linear regression analysis and data processing using the SPSS 25 application. The results of the research state that The variable Number of Tourists has a significant positive influence on labor absorption in the tourism industry in Medan City. The variable number of hotel rooms has a significant positive influence on labor absorption in the tourism industry in Medan City. The wage level variable for working in the tourism sector has a significant positive influence on labor absorption in the tourism industry in Medan City with a significant value.